Management Styles of Social Economy Female Leaders: Case Studies from Poland - Janusz REICHEL (Communications of International Proceedings, 2022)
Social enterprises in Poland are a relatively new phenomenon. Many of them are run by women. The author decided to check how the management of these entities looks like in the eyes of the women who run them, which is not yet covered by the literature. The analysis of individual characteristics possessed by leaders rather poorly explains the organizational reality and possible successes of leaders. However, it seems that leaders are different from other people, and research provides important insights on this. One of key manifestations of a manager's attribute is his/her management style. The study presented in the paper concerns the management styles demonstrated by the female leaders of social enterprises operating in central Poland. Attention was paid to the factors of success, obstacles standing on the way to the development of the organization, the characteristics of female leaders, management styles and their self-esteem. A qualitative study using the individual in-depth interview technique was conducted among 12 female leaders of social economy entities. The qualitative study was supplemented with elements of quantitative analysis, allowing for comparisons between the surveyed women. The female leaders present mainly consultative and participatory management styles, what seems to confirm the existing literature. The analysis shows allow to isolate different groups of social enterprise female managers based on their self-assessment of their approach to managing the organization but the legitimacy of such a division requires more further extensive quantitative research.
Keywords: female leaders; management styles; social economy; social enterprises